Prediction of worsening of skin fibrosis in patients with diffuse cutaneous systemic sclerosis using the EUSTAR database. Issue 6 (30th June 2014) - Maurer, Britta; Graf, Nicole; Michel, Beat A; Müller-Ladner, Ulf; Czirják, László; Denton, Christopher P; Tyndall, Alan; Metzig, Carola; Lanius, Vivian; Khanna, Dinesh; Distler, Oliver; ,
Abstract : Objectives: To identify predictive parameters for the progression of skin fibrosis within 1 year in patients with diffuse cutaneous SSc (dcSSc). Methods: An observational study using the EUSTAR database was performed. Inclusion criteria were dcSSc, American College of Rheumatology (ACR) criteria fulfilled, modified Rodnan skin score (MRSS) ≥7 at baseline visit, valid data for MRSS at 2nd visit, and available follow-up of 12±2 months. Worsening of skin fibrosis was defined as increase in MRSS >5 points and ≥25% from baseline to 2nd visit. In the univariate analysis, patients with progressive fibrosis were compared with non-progressors, and predictive markers with p<0.2 were included in the logistic regression analysis. The prediction models were then validated in a second cohort. Results: A total of 637 dcSSc patients were eligible. Univariate analyses identified joint synovitis, short disease duration (≤15 months), short disease duration in females/patients without creatine kinase (CK) elevation, low baseline MRSS (≤22/51), and absence of oesophageal symptoms as potential predictors for progressive skin fibrosis. In the multivariate analysis, by employing combinations of the predictors, 17 models with varying prediction success were generated, allowing cohort enrichment from 9.7% progressive patients in the whole cohort to 44.4% in the optimised enrichment cohort. Using a second validation cohort of 188 dcSSc patients, short disease duration, low baseline MRSS and joint synovitis were confirmed as independent predictors of progressive skin fibrosis within 1 year resulting in a 4.5-fold increased prediction success rate. Conclusions: Our study provides novel, evidence-based criteria for the enrichment of dcSSc cohorts with patients who experience worsening of skin fibrosis which allows improved clinical trial design.